Phylogenetic analysis, metabolic profiling, and environmental adaptation of strain LCG007: a novel Rhodobacteraceae isolated from the East China Sea intertidal zone - Cuizhu Liang; Jiahua Wang; Jie Liu; Zekai Wang; Junwei Cao; Xi Yu; Li Zhang; Jiasong Fang; Jiasong Fang (Frontiers in Microbiology)
Strain LCG007, isolated from Lu Chao Harbor's intertidal water, phylogenetically represents a novel genus within the family Rhodobacteraceae. Metabolically, it possesses a wide array of amino acid metabolic genes that enable it to thrive on both amino acids or peptides. Also, it could hydrolyze peptides containing D-amino acids, highlighting its potential role in the cycling of refractory organic matter. Moreover, strain LCG007 could utilize various carbohydrates, including mannopine and D-apiose—compounds primarily derived from terrestrial plants—demonstrating its capacity to degrade terrestrial organic matter. It could assimilate ammonia, nitrate and nitrite, and utilizes organic nitrogen sources such as polyamines, along with diverse organic and inorganic phosphorus and sulfur sources. Importantly, unlike very limited Sulfitobacter species that possess photosynthetic genes, the genomes of strain LCG007-affiliated genus and all Roseobacter species harbor photosynthetic gene clusters. This conservation was further supported by the significant impact of light on the growth and cell aggregation of strain LCG007, suggesting that acquirement of photosynthetic genes could play a crucial role in the speciation of their common ancestor. In terms of environmental adaptability, the genes that encode for DNA photolyase, heat and cold shock proteins, and enzymes responsible for scavenging reactive oxygen species, along with those involved in the uptake and biosynthesis of osmoprotectants such as betaine, γ-aminobutyric acid (GABA), and trehalose collectively enable strain LCG007 to survive in the dynamic and complex intertidal zone environment. Besides, the capacity in biofilm formation is crucial for its survival under conditions of oligotrophy or high salinity. This study enhances our comprehension of the microbial taxonomy within the Roseobacter clade affiliated cluster, their survival strategies in intertidal ecosystems, and underscores the significance of their role in nutrient cycling. It also highlights the crucial importance of photosynthetic metabolism for the speciation of marine bacteria and their ecological resilience.